2023
DOI: 10.3390/v15071433
|View full text |Cite
|
Sign up to set email alerts
|

Cetylpyridinium Chloride-Containing Mouthwashes Show Virucidal Activity against Herpes Simplex Virus Type 1

Abstract: The oral cavity is particularly susceptible to viral infections that are self-recovering in most cases. However, complications may appear in severe cases and/or immunocompromised subjects. Cetylpyridinium chloride (CPC)-containing mouthwashes are able to decrease the infectivity of the SARS-CoV-2 virus by disrupting the integrity of the viral envelope. Here, we show that CPC, as the active ingredient contained in commercialized, exerts significant antiviral activity against enveloped viruses, such as HSV-1, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…All in all, our results confirm the antiviral properties of CPC and CHX against IAV and include RSV as a susceptible microorganism to these two compounds. Given these results, the data available in the literature [5,8,9,11,[13][14][15][19][20][21]34], and the mechanisms of action of both CPC and CHX [10,22,[35][36][37][38] we could expect similar results for other enveloped respiratory viruses.…”
Section: Plos Onesupporting
confidence: 66%
“…All in all, our results confirm the antiviral properties of CPC and CHX against IAV and include RSV as a susceptible microorganism to these two compounds. Given these results, the data available in the literature [5,8,9,11,[13][14][15][19][20][21]34], and the mechanisms of action of both CPC and CHX [10,22,[35][36][37][38] we could expect similar results for other enveloped respiratory viruses.…”
Section: Plos Onesupporting
confidence: 66%
“…Seo et al demonstrated that CPC should induce hepatitis B virus (HBV) inhibition through inhibition of viral capsid assembly by conducting in vitro and in vivo assay [13]. Riveira-Muñoz et al demonstrated a favorable antiviral effect of CPC against herpes simplex virus type 1 (HSV-1) in antiviral activity test using HSV-1 and human papillomavirus (HPV) stocks and further anticipated that CPC could exert significant antiviral activity against enveloped viruses [14]. Danial et al demonstrated that CPC was active against susceptible and oseltamivir-resistant influenza strains.…”
Section: Introductionmentioning
confidence: 99%